Antimicrobial susceptibility pattern of urinary tract isolates of citrobacter species in a tertiary care hospital - K.L, Shobha; S.J, Akshatha; G.S, Amin; L, Ramachandra (International Journal of Pharmacology and Toxicology, 2014)
Introduction: The genus Citrobacter is a distinct group of aerobic Gram-negative bacilli from the Enterobacteriaceae family. It is an opportunistic pathogen that can cause diarrhea, septicemia, meningitis, urinary tract and respiratory system infection. Its isolation in the hospital settings is increasing. It is a present challenge to the clinical microbiologist because of their increased occurrence in nosocomial infection. Objectives: The current study was done to find out the prevalence and antibiotic susceptibility pattern of Citrobacter species from urinary tract isolates. Materials and Methods: Urine samples received from January 2013 to December 2013 were considered. A total of 9186 urine samples were considered, out of which 6381 were sterile and 2805 plates had growth.65(2.312%)of the growth plates had Citrobacter species growth. Citrobacter species were identified by conventional biochemical method. Antibiotic sensitivity test was performed by Kirby-Bauer Disc diffusion method. Results: Out of 65 patients female: male ratio was 17:15.5.The age groups were 0-9years; 8 patients(12.3%),10-19years;3 patients(4.615%),20-29years;11patients (16.9%),30-39years;6patients(9.28%),40-49years;12 patients(18.46%),50-59years;5patients(7.69%),?60years;20 patients(30.76%).The effective agent against Citrobacter species was found to be Imipenem (90.76%) then Cefoperazone-Sulbactum (89.23%) followed by Piperacillin-Tazobactam and Amikacin (87.69%).6 Multidrug resistant strains and 8 were ESBL producers. Conclusion: From the study it was seen that multidrug resistant strains are emerging. Proper surveillance in the antimicrobial sensitivity of Citrobacter was required. The age group 60 and above was found in majority to have culture positive Citrobacter spp. Depending on antibiotic sensitivity pattern of Citrobacter isolates, the antibiotics should be used. Proper infection control measures should be taken to prevent the spread of the pathogen. Keywords: Antibiotic Susceptibility, Citrobacter Spp, Multi-Drug Resistant Bacteria, Urinary Tract Infections.